The wingless gene is required for embryonic brain development in Drosophila. - Richter, S.; Hartmann, B.; Reichert, H. (Development genes and evolution, 1998)
We have studied the role of the wingless gene in embryonic brain development of Drosophila. wingless is expressed in a large domain in the anlage of the protocerebrum and also transiently in smaller domains in the anlagen of the deutocerebrum and tritocerebrum. Elimination of the wingless gene in null mutants has dramatic effects on the developing protocerebrum; although initially generated, approximately one half of the protocerebrum is deleted in wingless null mutants by apoptotic cell death at late embryonic stages. Using temperature sensitive mutants, a rescue of the mutant phenotype can be achieved by stage-specific expression of functional wingless protein during embryonic stages 9-10. This time period correlates with that of neuroblast specification but preceeds the generation and subsequent loss of protocerebral neurons. Ectopic wingless over-expression in gain-of-function mutants results in dramatically oversized CNS. We conclude that wingless is required for the development of the anterior protocerebral brain region in Drosophila. We propose that an important role of wingless in this part of the developing brain is the determination of neural cell fate.